2020
DOI: 10.1080/20013078.2020.1806444
|View full text |Cite
|
Sign up to set email alerts
|

A combined “eat me/don't eat me” strategy based on extracellular vesicles for anticancer nanomedicine

Abstract: A long-term and huge challenge in nanomedicine is the substantial uptake and rapid clearance mediated by the mononuclear phagocyte system (MPS), which enormously hinders the development of nanodrugs. Inspired by the natural merits of extracellular vesicles, we therefore developed a combined "eat me/don't eat me" strategy in an effort to achieve MPS escape and efficient drug delivery. Methodologically, cationized mannan-modified extracellular vesicles derived from DC2.4 cells were administered to saturate the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 85 publications
3
109
0
Order By: Relevance
“…Corroborating the previous findings with the research work recently carried out by Yang et al [11] and Belhadj et al [66] , it was also shown that the expression of the CD47 protein on the surface of exosomes endows them with the ability to evade phagocytosis and consequently to increase their circulating half-life. Yang et al [11] reported that CD47 overexpression in exosomes extended the half-life by 3-fold in the bloodstream, with no obvious in vivo toxicity or immunogenicity in mice at the different dosages and time points tested.…”
Section: Approaches For Extending Exosomes’ Half-lifesupporting
confidence: 75%
See 1 more Smart Citation
“…Corroborating the previous findings with the research work recently carried out by Yang et al [11] and Belhadj et al [66] , it was also shown that the expression of the CD47 protein on the surface of exosomes endows them with the ability to evade phagocytosis and consequently to increase their circulating half-life. Yang et al [11] reported that CD47 overexpression in exosomes extended the half-life by 3-fold in the bloodstream, with no obvious in vivo toxicity or immunogenicity in mice at the different dosages and time points tested.…”
Section: Approaches For Extending Exosomes’ Half-lifesupporting
confidence: 75%
“…Yang et al [11] reported that CD47 overexpression in exosomes extended the half-life by 3-fold in the bloodstream, with no obvious in vivo toxicity or immunogenicity in mice at the different dosages and time points tested. Likewise, Belhadj et al [66] observed that the incorporation of CD47 in the surface membrane of exosomes reduce the endocytosis by macrophages, enhancing the uptake by the target tumor cells, prolonging the in vivo circulation time, lowering the distribution to the liver and spleen, and increasing tumor accumulation.…”
Section: Approaches For Extending Exosomes’ Half-lifementioning
confidence: 99%
“…Equally, the presence of certain receptors facilitates evasion from the host immune system. For instance, CD47 at the surface of engineered exosomes contributes to evasion from host immune cells during circulation in vivo [ 109 ]. Complex lipids also influence exosome targeting as observed in cancer cells.…”
Section: Transport and Biodistributionmentioning
confidence: 99%
“…In the therapeutic anticancer area, Belhadj et al . 160 exploited a combined “eat me/don't eat me” tactic to reduce endocytosis of macrophages. For the “eat me” component, EVs extracted from DC2.4 cells were modified with cationic mannan to saturate the MPS.…”
Section: Targeted Delivery Of Therapeutic Extracellular Vesicles In Hmentioning
confidence: 99%